Investigation of effect on cross-flow heat exchanger with air flow non-uniformity under low Reynolds number - Kai Shen; Zhendong Zhang; Ziqing Zhang; Youwen Yang (Advances in Mechanical Engineering, 2017)
In this study, the theoretical and experimental study of a cross-flow heat exchanger is carried out based on the theory of porous media under low Reynolds number. The accuracy of the mathematical calculation model is verified by experiments. Pressure drop in air side and efficiency of heat exchanger are analyzed with mathematical models of various non-uniform air flows under low Reynolds number. The responses are found influences of air flow non-uniformity on pressure drop and efficiency of heat exchanger have certain rules. The difference in pressure drops between non-uniform air flows and evenly distributed air flows is linearly related to variance S 2 of non-uniformity. And the increasing rate of resistance energy consumption difference between non-uniform air flows and evenly distributed air flows is approximately linearly related to the relatively non-uniform coefficient squared i of non-uniformity. The descent range of heat transfer efficiency has exponential relation to the relatively non-uniform coefficient i .